Impact of green financial funding on improving the financial efficiency of a sample of companies listed on the Iraq stock exchange - Shamkhi Mohan, Russell; Munshid Muhammad, Asaad (Edelweiss Applied Science and Technology, 2024)
The aim of this research is to identify the impact of green financing on financial efficiency by highlighting the importance of financing green activities in supporting the financial efficiency of banks. In this research, the authors adopted the descriptive analytical method and the statistical method, where (75) questionnaires were distributed to a research sample consisting of three banks: Al-Ahli Bank of Iraq, Middle East Bank, and North Bank. The questionnaires were transcribed and analyzed using Microsoft Excel. The research concluded that green financing contributes to financing sustainable activities and protecting the environment. The research also found that the interest in green financing enhances the efficiency of bank management in facing risks, while green financing has a weak impact on the performance and financial efficiency of banks. The research recommends that banks focus on sustainability and renewable energy sectors, increase investors’ and customers’ awareness of green activities, and emphasize the importance of green financing in achieving sustainable development.